Cast iron comprising niobium particles and method for producing cast iron
By incorporating 0.01 to 1% by mass of niobium particles into the cast iron and preparing improved cast iron by in situ reaction, the problem of the difficulty of dispersing and safety risks of nanoparticles in cast iron in the prior art is solved, and the improved mechanical properties of cast iron and the safety and flexibility of industrial methods are achieved.
Patent Information
- Application Number
- CN202380055380.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-03
- Filing Date
- 2023-06-05
- Publication Date
- 2025-03-07
AI Technical Summary
The prior art faces problems of high concentration, high purity and precise particle size distribution characteristics when incorporated into cast iron, and nanoparticles have problems such as cohesion, difficulty in dispersion and safety risks in industrial use.
The niobium particles at a concentration of 0.01 to 1 mass % were incorporated in the steps before cast iron solidification, and improved cast iron was prepared by in-situ reaction, thereby achieving better nanoparticle dispersion and safety.
Improved mechanical properties of cast iron are achieved, including improved ultimate tensile strength and yield stress, and provide greater safety and flexibility in industrial methods.
Smart Images

Figure CN119585455A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of materials engineering and nanotechnology. More specifically, the present invention discloses an improved cast iron and a method for its preparation. The method of the present invention comprises the incorporation of niobium particles in a step prior to the solidification of the cast iron, and therefore has several advantages over corresponding industrial methods, is applicable to existing foundries, and does not require structural modifications. The product of the present invention has significant properties. In one embodiment, the product of the present invention is called "Steeron" because, although it is cast iron, it has the properties of steel. The product comprises cast iron with niobium particles, has a determined composition, shows improved properties and is beneficial in a variety of applications. Background Art
[0002] The incorporation of particles into molten metal is a technical problem which has not yet been satisfactorily solved and is the subject of intensive research.
[0003] In the specific area of cast iron, various approaches have been investigated and tried in order to improve the properties of the final product. One approach has been to try to incorporate nanoparticles of various materials. However, the large-scale use of nanoparticles still faces multiple limitations, the first of which is the inability to obtain high concentrations, high purity, precise particle size distribution characteristics or even simply large-scale available nanoparticle formulations. In addition, there are several other technical problems that limit the industrial use of nanoparticles, including the tendency to agglomerate, the difficulty of dispersion, the risks associated with possible dispersion in the air / environment, and the still little-known effects caused by human or animal contact with nanoparticles.
[0004] The difficult problems of mixing / dispersing / homogenizing additives, especially those containing nanoparticles, during the processing of metals and special steels have long been known and different approaches have been attempted to solve said problems.
[0005] When searching for prior art in the scientific and patent literature, the following relevant documents were found:
[0006] CN105414497 provides detailed information on the technical difficulties of dispersing additives when manufacturing special steels. The aforementioned document discloses a device developed specifically to solve this problem, which includes a pipeline, a feeder (with a valve welded to the side of the opening) and a thin sealed and welded pipeline, the end of which is towards the center of the other pipeline opening to ensure the passage of air or argon to form a negative pressure, thereby allowing the fine powder of the additive to be added to the liquid medium of the steel (molten). The device provides for regulating the uniform addition of the additive. The document does not disclose or anticipate the present invention.
[0007] JP3321491, entitled "Method for adding rare earth element to molten steel and additive", discloses a safe method for adding an additive to molten steel. The additive is prepared by filling a container with alloy powder containing rare earths, copper and aluminum. The container is made of a carbon steel or stainless steel hollow rod. The method of adding the additive consists of continuously adding the additive to the molten steel during the casting stage. This document does not disclose or anticipate the present invention.
[0008] US4892580 discloses a lead-containing additive in the form of filaments for obtaining modified steel. The additive (consisting of a metal coating and finely divided material) is in the form of filaments, and the finely divided material contains metallic lead or a lead alloy in addition to a material that releases CO2 at molten steel temperatures. This document does not disclose or anticipate the present invention.
[0009] RU2569621 discloses a method for preparing niobium-containing steel. The method comprises the steps of melting the steel in a vessel and forming a layer 200 mm thick. During the treatment of the metal outside the furnace, ferroniobium is added in a proportion of 0.01 to 1 kg per ton of metal. This document does not disclose or anticipate the present invention.
[0010] US 3860777 discloses a method of welding low alloy steel containing niobium. In the aforementioned document, a weld deposit having improved resistance and hardness compared to similar weld deposits previously known is obtained. The method comprises adding controlled amounts of vanadium and / or titanium, as well as other alloying elements, to the molten metal to form a deposit having a controlled concentration compared to the existing niobium concentration. The document does not disclose or anticipate the present invention.
[0011] WO 92226675 discloses a ferroniobium alloy and a niobium additive for steel, cast iron and other metal alloys. The microstructure of the ferroniobium alloy comprises a eutectic matrix (E) and a main component (N) as a niobium-rich solid solution, which requires a chemical composition of 75% to 95% niobium, 5% to 25% iron, with the following maximum impurity contents: tantalum 0.1%, silicon 3%, aluminum 1% and tin 0.15%. This additive can be used to add niobium to steel, cast iron and other materials. The document does not disclose or anticipate the present invention.
[0012] A pending patent application BR102021016247-3, still confidential and with common inventors to the present invention, discloses a niobium nanoparticle formulation obtained by a top-down process. The formulation also includes the following technical features: particles entirely within the nanometer size distribution range; high purity; industrial scale, economically viable at a moderate cost. The nanopowder formulation has a very high purity because the process does not add impurities or result in the formation of reaction products, which is the case with prior art bottom-up (or synthetic) processes. This document does not disclose or anticipate the present invention.
[0013] Pending patent application BR 102022002639-4 (filed by IHR in February 2022, with the same inventors, and still confidential) discloses a useful premix for nanoparticle formulations of different materials. In said document, which is incorporated herein by reference, nanoparticle premixes with specific composition, purity and particle size distribution characteristics are described for many applications and solving several technical problems, including facilitating dispersion in other substances and facilitating use in industrial processes. This document does not disclose or anticipate the present invention.
[0014] The paper by Luiz, TM (2019) (Synthesis of Nb2O5 nanoparticles for application in oxide dispersion hardened materials) describes a material formed of pure Fe (i.e., 99.6% purity) containing Nb2O5 nanoparticle reinforcements at concentrations of 0.25, 0.5, 1.0, 5.0 and 10.0 wt.%. The matrix used in the paper is pure iron, which has a significantly different composition from cast iron and is completely different from the method of the present invention applied to cast iron.
[0015] The article (Effect of niobium in medium alloyed ductile cast irons) by Bedolla-Jacuinde A. and Hernandez BX (2003) discloses a method for obtaining ductile iron including the addition of niobium particles. However, unlike the present invention, Fe-Nb particles are added to the cast iron before the green sand casting process. In addition, the aluminum mentioned in the document is used to deoxidize the alloy, and this use is different from the method used in the present invention.
[0016] It can be inferred from the literature searched that no literature was found that anticipated or suggested the teachings of the present invention. Summary of the invention
[0017] The present invention provides a new cast metal material which provides solutions to several disadvantages of the prior art. The present invention also discloses a method which provides significant improvements over similar methods.
[0018] One of the objects of the present invention is to provide a cast iron having improved mechanical properties.
[0019] In one embodiment, the present invention provides a cast iron comprising niobium particles in a concentration of 0.01 to 1 mass %. In one embodiment, the cast iron comprises niobium pentoxide nanoparticles.
[0020] In one embodiment, the improved cast iron of the invention is ductile iron, while in another embodiment it is grey iron. In both cases, the product of the invention has improved physicochemical and mechanical properties.
[0021] In one embodiment, the product of the present invention achieves the same ultimate tensile strength or yield stress level using a smaller amount of metallic material in the corresponding component, thereby achieving the same mechanical properties at a lower relative weight (mass).
[0022] In one embodiment, the product of the invention is in the form of an ingot, billet or other solid cast iron structure having improved thermal properties.
[0023] Another object of the present invention is to provide an industrial process for the manufacture of cast iron doped with niobium particles, which provides easier dispersion of the nanoparticles in the metal, greater safety in the industrial process, and ease of use on a large scale. In one embodiment, the process allows the preparation of improved cast iron by in-situ reaction, thus providing greater safety and flexibility in the industrial process, and ease of use on a large scale.
[0024] Another object of the invention is a method for obtaining cast iron comprising, before pouring the molten matrix, adding niobium particles in a concentration ranging from 0.01 to 1% by mass.
[0025] In some embodiments, the methods of the present invention provide reduced rechupes, better homogenization of particles in the melt, standardized metal alloys (baseline), and / or the production of parts with complex geometries.
[0026] These and other objects of the present invention will be immediately apparent to those skilled in the art and will be described in detail hereinafter. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The following figures are shown:
[0028] Figure 1The Zeta potential of aluminum particles is shown as a function of pH. The Zeta potential modulus (mV) is an indicator of particle stability. The larger the Zeta potential modulus, the more stable the particle.
[0029] Figure 2 The Zeta potential of niobium pentoxide particles is shown as a function of pH.
[0030] Figure 3 The particle size distribution results of aluminum particles measured using a Cilas apparatus are shown.
[0031] Figure 4 The SEM (scanning electron microscope) results of the metal mixture after mixing for 5 hours are shown, with magnifications of 3.11 kx and 2.01 kx at 10.0 kV, respectively, where the field of view is 89.1 μm and 138 μm in BSE mode, the WD is 9.63 mm, and the results are obtained on a VEGA3 TESCAN device.
[0032] Figure 5 The EDS (Energy Dispersive Spectroscopy) results of the metal mixture after 5 hours of mixing are shown. The EDS shows the ratio of each element in the metal mixture.
[0033] Figure 1 Photographs of Al "bunchlets" and A4 aluminum foil are shown, as described in detail in Tables 1 and 2.
[0034] Figure 2 Illustrative photographs showing an embodiment of the method for obtaining FoFo of the present invention in green sand: in A), the addition of "bundles" to the mold before pouring the melt is shown; in B), the pouring of the melt into the mold containing the "bundles" is shown.
[0035] Figure 3 A photograph of the casting assembly poured into three green sand molds is shown.
[0036] Figure 4 Photographs describing an embodiment of the method for obtaining the FoFo of the present invention in a cold-box, manual production line are shown: in A), a mold to which "bunchlets" have been added before pouring is shown; in B), a panoramic photo of the production line with several molds is shown; in C), detailed information on pouring the melt onto the mold containing the "bunchlets" is shown.
[0037] Figure 5 Photos of the cold box mold for two cases are shown. In A), the bottom of experimental condition P1 is shown (left); in B), the side of experimental condition P1 is shown (right).
[0038] Figure 6Photographs showing two situations for adding niobium pentoxide nanoparticles in a cold box mold. In A), the situation of chopped P1 is shown (left); in B), the situation of 9 parts of P1 is shown (right).
[0039] Figure 7 Microscopic images of etched and unetched samples are shown. In A), B1 is shown unetched (left); in B), it is shown etched (right).
[0040] Figure 8 Microscopic images of etched and unetched samples are shown. In A), B2 is shown unetched (left); in B), it is shown etched (right).
[0041] Fig. 9 Microscopic images of etched and unetched samples are shown. In A), B3 is shown unetched (left); in B), it is shown etched (right).
[0042] Fig.10 Microscopic images of etched and unetched samples are shown. In A), P1 is shown unetched (left); in B), it is shown etched (right).
[0043] Fig.11 A graph of tensile strength results in MPa under different test conditions is shown.
[0044] Fig.12 Photographs showing another embodiment of the improved FoFo production process in a green sand mould. In A) and B) images of the "bunches" placed in a green sand mould before pouring the casting are shown.
[0045] Fig.13 A photograph showing another embodiment of the improved FoFo preparation method is shown, which shows an image of the effect of chopped Nb2O5+Al nanoparticles.
[0046] Fig.14 Shows pouring and inoculation A photo of an implementation method of obtaining gray FoFo.
[0047] Fig.15 A cross-sectional photograph of a grey FoFo ingot obtained by the method of the present invention is shown. The highlighted area shows detailed information of the macroscopic pores.
[0048] Fig.16 Three photographs of test samples (CP) of grey FoFo prepared by the method of the present invention for tensile testing purposes are shown.
[0049] Fig.17Graph showing the Brinell hardness of the grey FoFo samples tested.
[0050] Fig.18 Microscopic images at 100x magnification of a grey FoFo sample obtained by the method of the present invention are shown. The sample logo is visible in all five images.
[0051] Fig.19 Microscopic images at 100x magnification of a grey FoFo sample etched with 3-4% nital (Nital) obtained by the method of the invention are shown. The sample logo is visible in each of the five images.
[0052] Fig. 20 Shown are etch micrographs of samples P6-P and B. The sample logo is visible in each of the two images.
[0053] Fig.21 In A) the dimensions of the CP are shown; in B) an image of a spheroidal graphite FoFo CP prepared for tensile testing is shown.
[0054] Fig. 22 A graph of yield strength and tensile strength data for ductile iron FoFo samples is shown.
[0055] Fig.23 An image of the elongation data for a spheroidal graphite FoFo sample is shown.
[0056] Fig.24 Microscopic images of etched and unetched parts are shown. The sample logo is visible in each of the four images.
[0057] Fig.25 The ultimate tensile strength and yield strength data test images of two experimental conditions (B and P6-P) are shown.
[0058] Fig.26 The Zeta potential of aluminum particles is shown as a function of pH. The Zeta potential modulus (mV) is an indicator of particle stability. The larger the Zeta potential modulus, the more stable the particle.
[0059] Fig. 27 The Zeta potential of niobium pentoxide particles is shown as a function of pH.
[0060] Fig.28 The particle size distribution results of aluminum particles measured using a Cilas apparatus are shown.
[0061] Fig.29 SEM (scanning electron microscope) results of the metal mixture after 5 hours of mixing are shown, with magnifications of 3.11 kx and 2.01 kx at 10.0 kV, respectively.
[0062] Fig.30 The EDS (Energy Dispersive Spectroscopy) results of the metal mixture after 5 hours of mixing are shown. The EDS shows the ratio of each element in the metal mixture.
[0063] Fig.31 A comparative chart of the average ultimate tensile strength (UTS) results for Melts 0 through 19 shown in Table 24 is shown. DETAILED DESCRIPTION
[0064] The product of the invention is a cast iron having improved properties due to the addition of niobium particles.
[0065] In the context of the present invention, the expression "niobium particles" covers various chemical entities containing niobium, including metallic niobium; oxides, hydrates, hydrides, carbides or nitrides of niobium; alloys of ferroniobium or niobium with other metals or transition metals; or combinations thereof. Also included are niobium pentoxide (Nb2O5), NbO2, NbO and FeNb. They can be micron particles, submicron particles or nanoparticles.
[0066] In one embodiment, the product of the present invention is in the form of an ingot, billet or other solid structure having a finer and uniform structure, without exhibiting macroscopic porosity or shrinkage cavities.
[0067] In one embodiment, the product of the invention is in the form of an ingot, billet, or other solid cast iron structure having increased ultimate tensile strength without reducing other mechanical properties (eg, yield strength, elongation) and ductility.
[0068] In one embodiment, the product of the present invention is in the form of an ingot, billet, or other solid cast iron structure having increased yield strength without compromising other mechanical properties.
[0069] Those skilled in the art will recognize that this unexpected increase in tensile strength without reducing ductility is a significant technical effect of the present invention.
[0070] In one embodiment, the product of the present invention is in the form of an ingot, billet, or other solid cast iron structure having improved thermal properties.
[0071] In a first aspect, the present invention provides a cast iron comprising niobium particles in a concentration of 0.01 to 1 mass %.
[0072] In one embodiment, the concentration of niobium particles is 0.01 to 0.5 mass%. In one embodiment, the concentration of niobium particles is 0.02 to 0.4 mass%. In one embodiment, the concentration of niobium particles is 0.03 to 0.3 mass%. In one embodiment, the concentration of niobium particles is 0.04 to 0.2 mass%. In one embodiment, the concentration of niobium particles is 0.05 to 0.2 mass%. In one embodiment, the concentration of niobium particles is 0.07 to 0.14 mass%.
[0073] In one embodiment, the niobium particles consist of niobium pentoxide, niobium, FeNb, or a combination thereof. In one embodiment, the niobium particles consist of niobium pentoxide.
[0074] In one embodiment, the cast iron of the present invention further comprises aluminum in a concentration of 0.01 to 1 mass %.
[0075] In one embodiment, the concentration of aluminum is 0.01 to 0.5 mass%. In one embodiment, the concentration of aluminum is 0.01 to 0.044 mass%. In one embodiment, the concentration of aluminum is 0.01 to 0.037 mass%. In one embodiment, the concentration of aluminum is 0.02 to 0.037 mass%. In one embodiment, the concentration of aluminum is 0.02 mass%.
[0076] In one embodiment of the present invention, the niobium particles are particles having a particle size distribution characteristic in the nanometer range. In one embodiment, the niobium particles are particles having a particle size distribution characteristic in the nanometer range. 90 Particle size distribution characteristics Particles with a size distribution in the range of hundreds of nanometers.
[0077] In one embodiment, the niobium particles are niobium pentoxide nanoparticles or FeNb nanoparticles.
[0078] In one embodiment, the cast iron is ductile iron or grey cast iron.
[0079] In one embodiment, the cast iron of the present invention exhibits at least a 7% increase in yield stress compared to the original cast iron; and / or at least an 11% increase in tensile strength compared to the original cast iron.
[0080] In one embodiment, the cast iron of the present invention is selected from:
[0081] - Grey cast iron with addition of 0.1% Nb2O5, finer and shorter graphite, 95% pearlite matrix and 5% ferrite; or
[0082] - Spheroidal graphite FoFo with addition of 0.1 wt.% Nb2O5, VI (78%) and V (22%) graphite (45 spheroidal graphite / mm 2, Models 5 and 6, 100% modular), 89% pearlite matrix and 11% ferrite.
[0083] In the present invention, a stoichiometric balance is set in the premix composition, thereby enabling alloys with tailored properties to be obtained, as can be seen from the following non-limiting examples.
[0084] The method of the present invention provides for in situ reaction of niobium particles and other constituents with the cast iron, thereby providing for the formation of other forms of niobium in the cast iron microstructure.
[0085] In one embodiment, the method of the present invention minimizes or eliminates the formation of shrinkage cavities and solidification voids (vazios de ).
[0086] In one embodiment, the method of the present invention provides for the formation of an ingot, billet or other solid structure having a finer and more uniform structure.
[0087] In one embodiment, the method of the present invention provides for modification of the chemical properties of a component into which the particles are incorporated.
[0088] In a second aspect, the invention presents a method for obtaining cast iron comprising, before pouring the molten matrix, adding niobium particles in a concentration ranging from 0.01 to 1% by mass.
[0089] In one embodiment, the concentration of niobium particles is 0.01 to 0.5 mass%. In one embodiment, the concentration of niobium particles is 0.02 to 0.4 mass%. In one embodiment, the concentration of niobium particles is 0.03 to 0.3 mass%. In one embodiment, the concentration of niobium particles is 0.04 to 0.2 mass%. In one embodiment, the concentration of niobium particles is 0.05 to 0.2 mass%. In one embodiment, the concentration of niobium particles is 0.07 to 0.14 mass%.
[0090] In one embodiment, the niobium particles are particles having a particle size distribution characteristic in the nanometer range. In one embodiment, the niobium particles are particles having a particle size distribution characteristic in the nanometer range. 90 Particle size distribution characteristics Particles with a size distribution in the range of hundreds of nanometers.
[0091] In one embodiment of the method of the present invention, the step of adding niobium particles is performed by adding a premix comprising niobium and aluminum particles.
[0092] In one embodiment, the concentration of aluminum is 0.01 to 1 mass%. In one embodiment, the concentration of aluminum is 0.01 to 0.1 mass%. In one embodiment, the concentration of aluminum is 0.01 to 0.044 mass%. In one embodiment, the concentration of aluminum is 0.01 to 0.041 mass%. In one embodiment, the concentration of aluminum is 0.01 to 0.037 mass%. In one embodiment, the concentration of aluminum is 0.01 to 0.034 mass%. In one embodiment, the concentration of aluminum is 0.02 to 0.037 mass%. In one embodiment, the concentration of aluminum is 0.02 to 0.034 mass%. In one embodiment, the concentration of aluminum is 0.02 mass%.
[0093] In one embodiment of the process of the present invention, the aluminum is powdered, crushed, ground or shredded.
[0094] In one embodiment of the process of the present invention, the premix comprising niobium and aluminum particles is added by at least one of the following means:
[0095] - Added to the mold before pouring the melt;
[0096] - Added to the transfer ladle before pouring the melt;
[0097] - Add at the entrance of the mold feed channel before pouring the melt;
[0098] - added to the furnace before pouring the melt; or
[0099] - Added to the spray stream together with the inoculant.
[0100] The time of addition of the premix is selected according to the process (e.g. mold size, geometric complexity, etc.). Furthermore, since these are very small portions of the material, the time of addition is also determined by the dispersibility, taking into account the above parameters. Depending on the process, a combination of factors is required to determine the optimal time of addition.
[0101] To better illustrate the above timing, in embodiments where the premix is added to the mold prior to pouring the melt, this method may be more appropriate when the part to be molded is in a vertical position and has sufficient mass to ensure dispersion of the premix.
[0102] In embodiments where the premix is added to the transfer ladle prior to pouring the melt, this approach may be more appropriate where the process permits.
[0103] In embodiments where the premix is added to the mold at the inlet of the feed channel prior to casting the melt, this approach may be more appropriate when the mold box is used for only one part.
[0104] In embodiments where the premix is added to the furnace prior to pouring the melt, this approach may be more appropriate if process temperatures permit.
[0105] In embodiments where a premix is added to the stream along with the inoculant, this approach may be more appropriate if plant processing permits.
[0106] In one embodiment of the method of the present invention, the aluminum is in the form of particles having a particle size distribution characteristic in the nanometer or micrometer range. In one embodiment, the aluminum is in the form of particles having a particle size distribution of hundreds of nanometers to tens of micrometers. 90 Particle size distribution characteristics.
[0107] In one embodiment of the method of the present invention, the premix comprises Nb2O5 and Al / Nb2O5 in a molar ratio of 1 to 5 to provide an in-situ reaction between aluminum and niobium pentoxide. In one embodiment, the premix comprises Al / Nb2O5 in a molar ratio of 1 to 4.33. In one embodiment, the premix comprises Al / Nb2O5 in a molar ratio of 2 to 4. In one embodiment, the premix comprises Al / Nb2O5 in a molar ratio of 3 to 3.67. In one embodiment, the premix comprises Al / Nb2O5 in a molar ratio of 3.33.
[0108] In one embodiment, the method of the present invention further comprises the step of adding a FeSiCaBa or FeSiCaBaZr inoculant at a ratio of 0.1 to 1 mass %. In one embodiment, the inoculant is FeSiCaBa and is added at a ratio of 0.2 to 0.6 mass %. In one embodiment, the inoculant is FeSiCaBa and is added at a ratio of 0.2 to 0.4 mass %.
[0109] In one embodiment, the method of the present invention further comprises the step of adding a carburizing agent to the molten charge. In one embodiment, the carburizing agent is natural or synthetic graphite.
[0110] In one embodiment, the method of the present invention further comprises the step of adding waste material to the molten charge.
[0111] Example
[0112] The embodiments presented herein are intended only to illustrate some of the various ways of implementing the invention and are not intended to limit the scope of the invention.
[0113] Example 1 - Preparation of Y-shaped grey FoFo ingot
[0114] In this example, Y-shaped ingots each having a mass of 5.5 kg were prepared in green sand and in a cold box using ash FoFo according to the conditions described in Tables 1 and 2.
[0115] Table 1: Number of Y-components in the respective experimental conditions.
[0116]
[0117] Table 2: Number of Y-components in the respective experimental conditions.
[0118]
[0119] The concentrations of the materials used in the experiments are detailed in Tables 3 to 5 below.
[0120] Table 3: Changes in Nb2O5-dispersing medium content in the first inoculation scheme (0.1 mass %).
[0121]
[0122] Table 4: Variation of the Nb2O5-nanoparticle content for the second inoculation scheme (0.01 to 0.5 mass %).
[0123]
[0124] Table 5: Variation of Nb2O5-nanoparticle content in the third inoculation scheme (0.1 mass %).
[0125]
[0126] When the base material is melted, 0.3 mass% FeSiCaBa inoculant is added to the ladle. In both methods, niobium pentoxide nanoparticles wrapped in aluminum film are added directly to the mold in the form of bundles, such as Figures 1 to 3 The amounts of niobium and aluminum pentoxide are as defined in Tables 3 to 5 above.
[0127] Each ladle has a capacity of 200 kg and approximately 35 ingots can be produced with each method. The pouring temperature of the cast iron at the start of ladle pouring corresponds to 1410°C in green sand and 1415°C in cold box, which corresponds to the production of 35 ingots. The pouring temperature at the end of ladle pouring corresponds to 1353°C in cold box, i.e. the production of remainders. The pouring time in both methods is between 5 and 7 seconds.
[0128] After casting the cast iron onto the niobium pentoxide, the cooling time was about 1 hour in green sand and about 4 hours in the cold box. Under these processing conditions, the added aluminum film was observed to float in both methods ( Figure 3 ), indicating that this form of addition is not the most appropriate.
[0129] Example 2 - Preparation of Y-shaped ingots - Changing the method of adding nanoparticles
[0130] In the present embodiment, the nanoparticle addition conditions were changed to obtain Y-shaped ingots each weighing 5.5 kg.
[0131] The concentrations of the various materials used in the experiments are detailed in Tables 3 to 5 of the previous examples.
[0132] Ingots were prepared with spheroidal graphite FoFo in a cold box according to the conditions described in Table 6.
[0133] Table 6: Number of Y-components in respective experimental conditions.
[0134]
[0135] In the experiment labeled B1, no niobium pentoxide and aluminum nanoparticles were added.
[0136] In the experiment marked B2, only an aluminum film (0.0372 mass %) was added.
[0137] In the experiment marked as P1, niobium pentoxide nanoparticles were added to the aluminum film (Al / Nb2O5=3.7 mol) under different conditions, the whole constituting the total amount of the experiment in Example 1.
[0138] 1) P1 bottom: Divide the aluminum film and nanoparticles into 7 equal parts and place them in layers on the bottom of the mold. Add niobium pentoxide nanoparticles to each layer of aluminum film ( Figure 5 A).
[0139] 2) P1 side: aluminum foil covering the inside of the mold and nanoparticles added on top ( Figure 5 B).
[0140] 3) Shredded P1: The aluminum foil was manually shredded with scissors to the smallest possible size and mixed with the nanoparticles at the bottom of the mold ( Figure 6 ).
[0141] 4) 9 parts of P1: Separate and weigh 9 parts of the same mass of bundle and add to the bottom of the mold ( Figure 6 A and B).
[0142] 5) 8 manual feeds P1: 1 bundle was separated and weighed according to the method carried out in Example 1. "8 times" corresponds to the number of "ladles" used in the method.
[0143] 6) P1 Repeat Example 1: Add a small bundle as used in the example as a control ( Figure 4 ).
[0144] While the base material was being melted, similar to Example 1, 0.3 mass % of FeSiCaBa inoculant was added to the ladle.
[0145] In this example, 7 parts were produced. The pouring temperature at the beginning of the ladle pouring corresponded to 1420°C. The temperature at the end of the ladle pouring was not measured, but estimates show that the temperature did not vary much at the end of the production. The pouring time for both methods was about 5-7 seconds. After pouring into the ladle, the cooling time was about 4 hours under all test conditions.
[0146] The results showed a significant improvement over the product obtained in Example 1.
[0147] Metallographic testing of etched and unetched samples showed different visual characteristics, such as Figures 7 to 10 shown.
[0148] In addition, mechanical testing showed significantly different properties. Table 7 summarizes the results of the tensile tests.
[0149] Table 7 - Tensile strength test results (in MPa).
[0150]
[0151] The data in Table 7 are well reflected in Fig.11 In, the tensile strength in MPa is shown.
[0152] Example 3 - Preparation of gray FoFo ingot
[0153] In this embodiment, long breads (30 kg each) are prepared. Ingots were prepared with ash FoFo in a sand mould according to the conditions described in Table 8.
[0154] Inoculation of 0.1 mass % Nb2O5 nanoparticles was performed via the T route (aluminum bundles) and the P route (chopped aluminum).
[0155] Table 8: Number of ingots per experiment.
[0156]
[0157] In Table 8, B = Baseline; P1 = Al / Nb2O5 (3.7 molar); P6 = Al / Nb2O5 (2 molar); the Al concentrations in P1 and P6 are equal to 372 and 203 ppm, respectively.
[0158] While the base material was being melted, FeSiCaBa inoculants were added to the ladle by spraying at 0.6 and 0.2 mass %, respectively.
[0159] The inoculation route using aluminum "bunches" (Route T) was performed as follows: Before pouring, an aluminum "bunch" containing nanoparticles was placed at the bottom of the mold, and each of the other four was fixed to the inner wall of the mold with a paper clip ( Fig.12).
[0160] The inoculation route using chopped aluminum (Route P) was performed as follows: chopped portions of aluminum foil and nanoparticles were added to the bottom of the mold ( Fig.13 ).
[0161] In all cases, the pouring temperature corresponded to 1406° C. and the pouring time was 8-9 seconds. After ingot preparation, cooling was carried out in air.
[0162] No aluminum flotation was observed in any of the inoculation routes ( Fig.14 ).
[0163] The results of these experiments using the Ash FoFo are described below. Reusable moulds taken directly from the furnace were prepared to control the chemical composition of the Ash FoFo. Table 9 shows the acceptable detection limits and chemical composition results analyzed by an optical emission spectrometer (OES, Q4 Tasman Series 2).
[0164] Table 9 - Acceptable detection limits and results for gray FoFo composition in two runs (top and bottom rows, respectively).
[0165] C Si Mn P S Ni Cr Mo Cu Sn Al Ti V Mg 3.45 1.95 0.25 0.0 0.07 0.0 0.0 0.0 0.27 0.025 0.0 0.0 0.0 0.0 3.60 2.20 0.40 0.08 0.10 0.10 0.10 0.01 0.35 0.040 0.02 0.03 0.01 0.01
[0166] C Si Mn P S Ni Cr Mo Cu Sn Al V Mg 3.532 2.1 0.368 0.026 0.088 0.015 0.047 0.003 0.262 0.026 0.004 0.002 0.0 3.549 2.058 0.4080 0.022 0.094 0.018 0.059 0.001 0.241 0.035 0.004 0.001 0.01
[0167] Pb B CE Cu Eq 0.001 0.0 4.241 0.762 0.001 0.0 4.242 0.866
[0168] The ingots of FoFo formulations (B, P1 and P6) showed internal macroscopic pores ( Fig.15 ).
[0169] CPs obtained with gray FoFo formulations (B, P1 and P6) showed macroscopic pores ( Fig.16 ), which made tensile testing impossible.
[0170] The Brinell hardness test was performed on the Cp of each formulation. Each Cp was measured five times. The average value and the corresponding deviation are shown in Fig.17 The formulation P6-P increased the hardness value by 3.4% on average compared to the base alloy, and the formulation P1 decreased the hardness value by 5.4% on average compared to the base alloy.
[0171] The samples were cut, ground and polished to a particle size distribution of 1 μm, and their microscopic images were obtained and observed under an optical microscope to evaluate the microstructure. Fig.18 shows a microscopic image of gray FoFo at 100x magnification, Fig.19 Shown is a microscopic image of a gray FoFo etched with 3-4% nital solution at 100x magnification.
[0172] Fig. 20 Microscopic images of the sample etched with 3-4% nital solution, which is sample P6-P that obtained the best mechanical property results, and baseline sample B are shown at a magnification of 100x. Fig. 20 In the graphite section, refined graphite and less ferrite can be seen in the P6-P sample compared to sample B. This refinement and less ferrite could be related to the improvement in the mechanical properties of hardness. Tensile testing would be required to assess if it follows the same behavior.
[0173] The metallographic analysis results show that the inoculation of niobium pentoxide nanoparticles has a tendency towards microstructural refinement. On the other hand, the results of mechanical testing of the hardness of gray FoFo are very promising and strongly suggest the continuation of additional research aimed at improving the technology.
[0174] Example 4 - Preparation of spheroidal graphite FoFo ingot
[0175] In this embodiment, long loaf-shaped ingots each having a mass of 30 kg were prepared. According to the conditions described in Table 10, ingots were prepared in a sand mold using spheroidal graphite FoFo.
[0176] Inoculation of 0.1 mass % Nb2O5 nanoparticles was performed via route T (aluminum bundles) and route P (shredded aluminum).
[0177] Table 10: Number of ingots per experiment.
[0178]
[0179] In Table 10, B = baseline; P1 = Al / Nb2O5 (3.7 molar); P6 = Al / Nb2O5 (2 molar); the Al concentrations in P1 and P6 are equal to 372 and 203 ppm, respectively.
[0180] While the base material was being melted, FeSiCaBa inoculants were added to the ladle by spraying at 0.6 and 0.2 mass %, respectively.
[0181] The inoculation route via aluminum "bunches" (Route T) was performed as described in Example 3.
[0182] The inoculation route via shredded aluminum (Route P) was performed as described in Example 3.
[0183] In all cases, the pouring temperature corresponded to 1445° C. and the pouring time was 9-10 seconds. After ingot preparation, cooling was carried out in air.
[0184] No aluminum flotation was observed in any of the inoculation routes ( Fig.14 ).
[0185] The results of these experiments using spheroidal graphite FoFo are described below. Reusable molds were prepared, taken directly from the furnace, to control the chemical composition of the spheroidal graphite FoFo. Table 11 shows the acceptable detection limits and chemical composition results analyzed by direct reading spectrometer (OES, Q4 Tasman Series 2).
[0186] Table 11 - Acceptable detection limits and ductile iron FoFo composition results
[0187] C Si Mn P S Ni Cr Mo Cu Sn Al Ti V Mg 3.55 2.3 0.0 0.0 0.0 0.0 0.0 0.0 0.1 0.0 0.0 0.0 0.0 0.036 3.73 2.65 0.45 0.08 0.018 0.1 0.1 0.01 0.2 0.02 0.015 0.03 0.01 0.055
[0188] C Si Mn P S Ni Cr Mo Cu Sn Al V Mg 3.55 2.4 0.256 0.028 0.014 0.013 0.032 0.003 0.059 0.006 0.011 0.001 0.038
[0189] Pb B CE Cu Eq 0.001 0.0 4.359 0.285
[0190] The ingots of formulations (B, P1 and P6) showed no internal macroscopic porosity.
[0191] Tensile tests were performed on four CPs of each formulation and the average values and respective deviations are shown in Fig. 22 and 23 Compared with the base alloy, the P6-P formulation resulted in an average improvement in fluidity and resistance of 5.4% and 12.6%, respectively.
[0192] Table 12 details the characteristics of the test samples. Fig.21 The specific conditions used in the test samples shown are indicated in bold.
[0193] Table 12—Characteristics of the test samples.
[0194]
[0195] Fig.24 The micrographs shown show the metallographic results for etched and unetched under Condition B (baseline) and P6-P.
[0196] The results of metallographic analysis show that the inoculation of niobium pentoxide nanoparticles has a tendency towards microstructural refinement. On the other hand, the results of mechanical tests on the yield strength and ultimate tensile strength of ductile graphite FoFo are very promising and strongly suggest the continuation of additional research aimed at improving the technology.
[0197] Example 5 - Nanostructured premix comprising niobium pentoxide nanoparticles.
[0198] For the preparation of P6 premix, the following materials were used:
[0199] Aluminium foil (80 g); and
[0200] ●Agitator;
[0201] • Attritor mill using zirconia balls (d = 200-300 μm, m = 800 g).
[0202] Implement the following steps:
[0203] 80 g of aluminum foil were comminuted in a blender. The comminuted foil (40 g) was ground in an Attritor mill in ethanol medium at 350 RPM for 22 h with the aid of zirconium oxide balls (d=200-300 μm, m=800 g).
[0204] The wet metal mixture was separated by a sieve with a pore size of 500 μm. Samples of the wet metal mixture below 500 μm were taken for determination of zeta potential and particle size.
[0205] Likewise, samples of the wet metal mixture below 500 μm were taken for particle size determination in a Cilas apparatus.
[0206] The wet metal mixture was dried in an oven at 80°C to obtain dry powder.
[0207] For the Nb2O5 suspension, the pH was adjusted to 6 using an aqueous ammonium hydroxide solution (pH 14) (experimentally measured solid content: 26% by mass, volume: 440 mL).
[0208] The particle size distribution of niobium pentoxide nanoparticles used in the preparation of the premix is d 10 =0.16μm, d 50 =0.35μm, d 90 =0.78μm.
[0209] The Nb2O5 suspension was mechanically stirred at 300 RPM, and 23 g of aluminum powder was gradually added thereto. After the addition of aluminum powder, stirring was maintained at 300 RPM for 5 h under pH monitoring.
[0210] After 5 hours of mixing, an increase in pH was observed. The pH of the final mixture remained at ~7.1.
[0211] After mechanical stirring for 2, 3, 4, and 5 h, the samples were removed from the mother suspension and dried in a vacuum oven at 80 °C to observe the intimate mixing state between the Al and Nb2O5 particles in the nanostructured premix.
[0212] Table 13 below records the mass ratio of Nb2O5 and Al nanoparticles:
[0213] Table 13 - Mass ratio of niobium and aluminum nanoparticles
[0214]
[0215] In view of the experiments performed, the mass ratio of nanoparticles:aluminum is preferably between 90.8:9.2 and 69.4:30.6.
[0216] Variations in the nanoparticle content in the premix for cast iron were also tested, as shown in Table 14 below.
[0217] Table 14 - Changes in Nanoparticle Content
[0218]
[0219] Example 6 - Premix Characterization
[0220] In one embodiment, the nanostructured premix is characterized. To this end, the wet metal mixture is separated using a sieve with a pore size of 500 μm. A sample of the wet metal mixture below 500 μm is taken to determine the zeta potential and particle size.
[0221] Fig.26 The Zeta potential of aluminum particles is shown as a function of pH. The Zeta potential modulus (mV) is an indicator of particle stability. The larger the Zeta potential modulus, the more stable the particle.
[0222] Fig. 27 The Zeta potential of niobium pentoxide particles is shown as a function of pH.
[0223] In view of the results of Zeta potential as a function of pH, the pH of the metal mixture was adjusted to 6 at the beginning of the step.
[0224] As also mentioned in Example 5, a sample of the wet metal mixture below 500 μm was also taken to determine the particle size in the Cilas apparatus.
[0225] Fig.28 The particle size distribution results of aluminum particles measured using a Cilas apparatus are shown.
[0226] The results of the particle size distribution tests performed on the Cilas equipment can be seen in Table 15 below:
[0227] Table 15 - Aluminum particle size distribution data
[0228] Particle distribution % Particle size (equivalent diameter) D10% 14.92μm D50% 39.77μm D90% 70.44μm D Mean 40.94μm
[0229] Fig.29 SEM (scanning electron microscope) results of the metal mixture after 5 hours of mixing are shown, with magnifications of 3.11 kx and 2.01 kx at 10.0 kV, respectively.
[0230] Fig.30The EDS (Energy Dispersive Spectroscopy) results of the metal mixture after 5 hours of mixing are shown. The EDS shows the ratio of each element in the metal mixture.
[0231] Example 7 - Nanostructured premix addition test
[0232] In order to test the nanostructured premixes of the previous examples, ingots ("loaf" shape) of ductile iron (Alloy F) were prepared. The mass of the set was about 27 kg and the green sand method was used.
[0233] The content of niobium pentoxide (nano, submicron and micron) relative to the base metal is 0.1 mass% (equivalent to 0.07 mass% Nb). The content of Al relative to the base metal is 0.020 mass% (sub-condition ( hipo)).
[0234] A premix containing nano, submicron and micron powder particles is added through filters. Each filter is located above the inlet of each feed channel of each die.
[0235] The inoculant was added when transferring the melt to the casting ladle (FeSiCaBa 0.6 mass%) (ladle inoculation) and when transferring the melt from the casting ladle to the respective moulds (FeSiCaBa 0.2 mass%) (spray inoculation).
[0236] The pouring temperature (when the ladle starts pouring) is 1406°C. The pouring time is 8 to 9 seconds. The cooling time of the billet is about 45 minutes.
[0237] In the case of spray inoculation, it was observed that part of the powder was thrown into the air when the melt was transferred from the casting ladle to the respective moulds. In the samples obtained from this method, part of the powder was observed to be retained along the respective feed channels.
[0238] Example 8 - Testing of Adding Nanostructured Premix to Transfer Ladle
[0239] Another addition route was tested. Ingots ("loaf" shape) of ductile iron (alloy G1) were produced. The mass of the batch was about 27 kg and the green sand method was used.
[0240] The content of niobium pentoxide (nano) relative to the base metal was 0.1 mass % (corresponding to 0.07 mass % of Nb), and the content of Al relative to the base metal was 0.020 mass % (sub-condition).
[0241] The aluminum-containing powdered premix is added through filters. Each filter is located above the inlet of each feed channel of each die.
[0242] The nanopowder mixture was added to a transfer ladle together with Al foil chopped and extruded into "pellets" (plus 1.3 mass % spheroidized FeSiMg).
[0243] Table 16 - Chemical composition of Alloy G1 (from reusable mold removed from ladle)
[0244]
[0245] The inoculant was added when transferring the melt to the casting ladle (FeSiCaBa 0.6 mass%) (ladle inoculation) and when transferring the melt from the casting ladle to the respective moulds (FeSiCaBa 0.2 mass%) (spray inoculation).
[0246] The pouring temperature (at the start of ladle pouring) was 1406°C. The pouring time was 8 to 9 seconds. The cooling time of the ingot was about 3 hours for the base sample group and about 45 minutes for the sample groups of P6 premix in the filter and chopped P6 premix in the ladle.
[0247] During the addition of the powdered aluminum-containing premix to the filter, part of the powder is thrown into the air during the spray inoculation.
[0248] No floating was observed in the samples produced by the ladle addition route.Tensile tests were performed on 15 samples of each billet (base, premix P6 and chopped P6).
[0249] The results of the mechanical evaluation are described as follows:
[0250] P6 premix through filter: On average, this approach resulted in a 5.8% increase in UTS (matrix: 500.6 MPa; P6 premix: 529.8 MPa) and a 13.4% increase in elongation (AL) (matrix: 13.4%; P6 premix: 15.2%).
[0251] Chopped P6 in ladle: On average, this approach resulted in a 54.7% increase in UTS (matrix: 500.6 MPa; chopped P6: 774.4 MPa) and a 41% decrease in AL (matrix: 13.4%; chopped P6: 7.9%).
[0252] Example 9 - Testing of Adding Nanostructured Premixes to Gray Cast Iron
[0253] Ingots ("loaf" shape) of grey cast iron (alloy G1) were produced. The mass of the group was about 27 kg and the green sand method was used.
[0254] The content of niobium pentoxide (nano) relative to the base metal was 0.1 mass % (corresponding to 0.07 mass % of Nb), and the content of Al relative to the base metal was 0.02 mass % (sub-condition).
[0255] The aluminum-containing powder premix is added through filters. Each filter is located above the inlet of each feed channel of each die.
[0256] The nanopowder mixture was added along with Al foil that was chopped and extruded into “pellets”.
[0257] The inoculant was added when transferring the melt to the casting ladle (FeSiCaBa 0.6 mass%) (ladle inoculation) and when transferring the melt from the casting ladle to the respective moulds (FeSiCaBa 0.2 mass%) (spray inoculation).
[0258] The pouring temperature (when the ladle starts pouring) is 1380-1440°C. The pouring time is 8 to 9 seconds. The cooling time of the billet is about 45 minutes.
[0259] During the addition of the powdered aluminum-containing premix to the filter, part of the powder is thrown into the air during the spray inoculation.
[0260] No floating was observed in the samples produced by this method. Tensile tests were performed on 9 test samples (for each alloy). Mechanical evaluations were performed on an MTS machine.
[0261] The results of the mechanical evaluation are described as follows:
[0262] P6 premix in the filter did not change the UTS (matrix: 242.3 MPa; P6 premix: 242.9 MPa), chopped P6 in the ladle reduced the UTS by 2% (matrix: 242.3 MPa; chopped P6, ladle: 237.3 MPa). The central area of the ingot showed lower resistance compared to the bottom and top areas.
[0263] Example 10 - Tests on heat treatment (tempering) in ductile iron
[0264] Ingots ("loaf" shape) of ductile iron (alloy G1) were produced. The mass of the group was about 27 kg and the green sand method was used.
[0265] The content of niobium pentoxide (nano) relative to the base metal was 0.1 mass % (corresponding to 0.07 mass % of Nb), and the content of Al relative to the base metal was 0.02 mass % (sub-condition).
[0266] The nanopowder mixture was added along with Al foil that was chopped and extruded into “pellets”.
[0267] The inoculant was added when transferring the melt to the casting ladle (FeSiCaBa 0.6 mass%) (ladle inoculation) and when transferring the melt from the casting ladle to the respective moulds (FeSiCaBa 0.2 mass%) (spray inoculation).
[0268] The pouring temperature (at the start of ladle pouring) was 1380 to 1440°C. The pouring time was 8-9 seconds. The cooling time of the ingot was about 3 hours for the matrix sample group and about 45 minutes for the P6 premix in the filter and the chopped P6 premix in the ladle sample groups.
[0269] The samples were heat treated. The samples were austenitized at 900°C for 1 h and then cooled to 260°C. Mechanical tests were performed on one sample (for each alloy).
[0270] The mechanical evaluation results are described as follows:
[0271] Chopped P6 in the ladle increased UTS by 14% (austempered base: 1011 MPa; chopped P6, ladle, austempered: 1151 MPa), LE by 5% (austempered base: 867 MPa; chopped P6, ladle, austempered: 909 MPa) and elongation (AL) by 150% (austempered base: 1%; chopped P6, ladle, austempered: 2.5%).
[0272] Tempering can "correct" the microstructure. Significant differences in the cooling rates of the original samples produce matrices with very different proportions of phases, which can lead to different microstructural transformation rates during tempering and affect the mechanical results.
[0273] Example 11 - Tests of Heat Treatment (Tempering) in Ductile Iron
[0274] Ingots ("loaf" shape) of ductile iron (alloy F) were produced. The mass of the group was about 27 kg and the green sand method was used.
[0275] The content of niobium pentoxide (submicron and micron) relative to the base metal is 0.1 mass % (equivalent to 0.07 mass % Nb). The content of Al relative to the base metal is 0.02 mass % (submicron). The content of micron FeNb relative to the base metal is 0.11 mass % (equivalent to 0.07 mass % Nb).
[0276] Submicron and micron premixes and FeNb powders were tested on individual filters located above the inlet of the individual die feed channels.
[0277] The inoculant was added when transferring the melt to the casting ladle (FeSiCaBa 0.6 mass%) (ladle inoculation) and when transferring the melt from the casting ladle to the respective moulds (FeSiCaBa 0.2 mass%) (spray inoculation).
[0278] The pouring temperature (when the ladle starts pouring) is about 1425° C. The pouring time is 8 to 9 seconds. The cooling time of the billet is about 45 minutes.
[0279] The samples were heat treated. The samples were austenitized at 900°C for 1 h and cooled to 260°C. One sample (for each alloy) was mechanically tested.
[0280] When the melt was transferred from the casting ladle to the respective moulds, part of the powder was observed to be thrown into the air during the spray inoculation. In the samples obtained by this method, part of the powder was observed to be retained along the respective feed channels.
[0281] Example 12 - Tests to Evaluate Submicron and Micron Particle Incorporation
[0282] Ingots ("loaf" shape) of ductile iron (alloy G1) were produced. The mass of the group was about 27 kg and the green sand method was used.
[0283] The content of niobium pentoxide (submicron and micron) relative to the base metal was 0.1 mass % (corresponding to 0.07 mass % of Nb). The content of Al relative to the base metal was 0.020 mass % (submicron).
[0284] The formulation was added to the ladle in the form of a mixture of powders (submicron or micron Nb2O5) and Al foil chopped and extruded into "pellets" (plus 1.3 mass % of spheroidized FeSiMg).
[0285] Table 17 - Chemical composition of Alloy G1 (from reusable mold removed from ladle)
[0286]
[0287] The inoculant was added when transferring the melt to the casting ladle (FeSiCaBa 0.6 mass%) (ladle inoculation) and when transferring the melt from the casting ladle to the respective moulds (FeSiCaBa 0.2 mass%) (spray inoculation).
[0288] The pouring temperature (when ladle pouring starts) was 1402°C (matrix test), 1418°C (submicron mixed test) and 1409°C (micron mixed test). The pouring time was 8 to 9 seconds. The cooling time of the ingot was about 45 minutes.
[0289] Mechanical testing was performed on 9 test samples / ingots. The mechanical evaluation results are as follows:
[0290] P6 premix through filter: On average, this approach resulted in a 5.8% increase in UTS (matrix: 500.6 MPa; P6 premix: 529.8 MPa) and a 13.4% increase in elongation (AL) (matrix: 13.4%; P6 premix: 15.2%).
[0291] Mechanical evaluation of samples incorporated with submicron mixtures: On average, submicron particles caused a 4% decrease in UTS (matrix: 624 MPa; chopped P6, submicron: 600 MPa), a 2% decrease in LE (matrix: 429 MPa; chopped P6, submicron: 421 MPa) and no change in elongation (AL) (matrix: 9%; chopped P6, submicron: 9%).
[0292] Mechanical evaluation of samples incorporated with the micron mixture: On average, the micron particles caused a 5% decrease in UTS (matrix: 624 MPa; chopped P6, micron: 595 MPa), a 1% increase in LE (matrix: 429 MPa; chopped P6, micron: 434 MPa) and no change in AL (matrix: 9%; chopped P6, micron: 9%).
[0293] Example 13 - Testing of Nanostructured Premix Added to Transfer Ladle
[0294] Another addition route was tested. Ingots ("loaf" shape) of ductile iron (alloy G1) were produced. The mass of the batch was about 24 kg and the green sand method was used.
[0295] The content of niobium pentoxide (nano) relative to the base metal was 0.1 mass % (corresponding to 0.07 mass % of Nb), and the content of Al relative to the base metal was 0.020 mass % (sub-condition).
[0296] The nano premix formulation and FeNb powder (plus 1.3 mass % of spheroidized FeSiMg) in powder form were added to a transfer ladle.
[0297] Table 18 - Chemical composition of Alloy G1 (from reusable mold removed from ladle)
[0298]
[0299] The inoculant was added when transferring the melt to the casting ladle (FeSiCaBa 0.6 mass%) (ladle inoculation) and when transferring the melt from the casting ladle to the respective moulds (FeSiCaBa 0.2 mass%) (spray inoculation).
[0300] The pouring temperature (when the ladle starts pouring) is 1380-1440°C. The pouring time is 8 to 9 seconds. The cooling time of the billet is about 45 minutes.
[0301] No floating was observed in the samples produced by the ladle addition route.Tensile testing was performed on 9 samples from each ingot.
[0302] The results of the mechanical evaluation are as follows:
[0303] Mechanical evaluation of alloy G1-P6 premixes: On average, P6 premix resulted in a 0.4% decrease in UTS (matrix: 651 MPa; P6 premix: 648 MPa), a 2.6% increase in LE (matrix: 439 MPa; P6 premix: 450 MPa), and a 11% decrease in AL (matrix: 7.3%; chopped P6: 6.5%).
[0304] Mechanical evaluation of alloy G1-FeNb: On average, FeNb increases UTS by 1.5% (matrix: 651 MPa; FeNb: 658 MPa), decreases LE by 0.8% (matrix: 439 MPa; FeNb: 447 MPa) and decreases AL by 0.9% (matrix: 7.3%; FeNb: 6.4%).
[0305] Example 14 - Variation of Niobium Pentoxide Content in Gray Cast Iron
[0306] Ingots ("loaf" shape) of grey cast iron (alloy G1) were produced. The mass of the group was about 24 kg and the green sand method was used.
[0307] The content of niobium pentoxide (nano) relative to the base metal was 0.1 mass % (corresponding to 0.07 mass % of Nb) and 0.2 mass % (corresponding to 0.14 mass % of Nb). Aluminum was not used in this example.
[0308] The formulation in nano powder form is added to the transfer ladle.
[0309] Table 19 - Chemical composition of alloys (from reusable moulds, removed from the melt in the furnace)
[0310]
[0311] The inoculant was added when transferring the melt to the casting ladle (FeSiCaBa 0.6 mass%) (ladle inoculation) and when transferring the melt from the casting ladle to the respective moulds (FeSiCaBa 0.2 mass%) (spray inoculation).
[0312] The pouring temperature (when the ladle starts pouring) is 1380 to 1440°C. The pouring time is 8 to 9 seconds. The cooling time of the billet is about 45 minutes.
[0313] No flotation was observed in the samples produced by the ladle addition route. No significant changes in mechanical properties were observed.
[0314] Example 15 - Evaluation of the Pearlitization Potential of Niobium
[0315] Ingots ("loaf" shape) + step specimens (mass of assembled ingot + step specimen, mass of assembled part is about 21 kg) and Y-shaped blocks of ductile iron (Alloy I) were prepared. The green sand method was used.
[0316] The content of niobium pentoxide (nano) relative to the base metal was 0.1 mass % (corresponding to 0.07 mass % of Nb), and the content of Al relative to the base metal was 0.02 mass % (sub-condition).
[0317] The formulation (containing aluminum from Alle) and FeNb powder were added in the form of a premix powder to a transfer ladle.
[0318] Table 20 - Chemical composition of Alloy I (from reusable mould, removed from ladle melt)
[0319]
[0320] The inoculant was added when transferring the melt to the casting ladle (FeSiCaBa 0.6 mass%) (ladle inoculation) and when transferring the melt from the casting ladle to the respective moulds (FeSiCaBa 0.2 mass%) (spray inoculation).
[0321] The pouring temperatures (at the start of ladle pouring) were 1380°C (matrix), 1408°C (P6 premix) and 1400°C (FeNb). The pouring time was 8 to 9 seconds. The cooling time of the billet was about 45 minutes.
[0322] No floating was observed in the samples produced by the ladle addition route.In the samples cut from the Y-blocks, micropores were observed in the reservoirs of all alloys and macropores were observed in the reservoirs of the alloys modified with the P6 premix and FeNb.
[0323] Three test specimens (center area) were processed per ingot.
[0324] The results of the mechanical evaluation are as follows:
[0325] Mechanical evaluation of Alloy I-P6 premix: On average, P6 premix resulted in a 5.2% decrease in UTS (matrix: 640.3 MPa; P6 premix: 637.7 MPa), a 3.3% increase in LE (matrix: 459 MPa; P6 premix: 489 MPa), and a 1.5% increase in AL (matrix: 6.57%; chopped P6: 6.67%).
[0326] Mechanical evaluation of Alloy I—FeNb: On average, FeNb increases UTS by 2.1% (matrix: 651 MPa; FeNb: 653.7 MPa), LE by 1.5% (matrix: 459 MPa; FeNb: 465.7 MPa), and AL by 1.5% (matrix: 6.57%; FeNb: 6.67%).
[0327] Two test specimens were machined for each Y-block.
[0328] The results of the mechanical evaluation are as follows:
[0329] Mechanical evaluation of Alloy I-P6 premix: On average, P6 premix resulted in a 2% increase in UTS (matrix: 498 MPa; P6 premix: 507.5 MPa), a 2% increase in LE (matrix: 320 MPa; P6 premix: 326 MPa), and a 10% decrease in AL (matrix: 18.2%; P6 premix: 16.3%).
[0330] Mechanical evaluation of Alloy I-FeNb: On average, FeNb increases UTS by 14% (matrix: 498 MPa; FeNb: 570 MPa), increases LE by 11% (matrix: 320 MPa; FeNb: 356 MPa), and decreases AL by 25% (matrix: 18.2%; FeNb: 13.7%).
[0331] Nine test specimens were processed per ingot ("loaf" shape).
[0332] The results of the mechanical evaluation are as follows:
[0333] Mechanical evaluation of Alloy I-P6 premix: On average, P6 premix resulted in a 17% increase in UTS (matrix: 654 MPa; P6 premix: 763 MPa), a 15% increase in LE (matrix: 414 MPa; P6 premix: 477 MPa), and a 16% decrease in AL (matrix: 7.5%; P6 premix: 6.3%).
[0334] Mechanical evaluation of Alloy I-FeNb: On average, FeNb increases UTS by 10% (matrix: 654 MPa; FeNb: 718 MPa), increases LE by 8% (matrix: 414 MPa; FeNb: 449 MPa), and decreases AL by 17% (matrix: 7.5%; FeNb: 6.2%).
[0335] Example 16 - Effect of Nanostructured Premix on Grey Cast Iron (Alloy FC 200)
[0336] Grey cast iron Y-blocks (alloy FC 200-FUCO FC 200 matrix) were prepared using the cold box method.
[0337] Two tests were performed: Test 0 corresponds to a furnace "clean" melt, and Test 1 corresponds to a melt in which a premix (Al from Alle) was added to the charge. The sample obtained from melt 0 was used as a baseline.
[0338] The content of niobium pentoxide (nano) relative to the matrix material was 0.1 mass % (corresponding to 0.07 mass % of Nb). The content of aluminum relative to the matrix material was 0.02 mass %. The content of the premix relative to the matrix material was 0.12 mass %.
[0339] A powdered nano premix containing aluminum is added to the furnace. The premix is added from the beginning to mid-charge.
[0340] The inoculant was added when the melt was transferred from the furnace to the casting ladle (FeSiCaBa 0.16 mass %).
[0341] Molten Charge 0: All FUCO FC 200 + All 1020 scrap + All carburizing agent (natural graphite).
[0342] Melt Charge 1: All FUCO FC 200 + all premix (0.12 mass %) + all 1020 scrap + all carburizing agent (natural graphite).
[0343] The bath temperature in the furnace was about 1450±10°C. The pouring temperature was about 1390±10°C. The pouring time was about 15s. For the cooling time of the block, the cooling time was overnight to room temperature. In the samples produced by this method, no premix floating was observed.
[0344] Mechanical evaluation: On average, P6 premix resulted in a 36.5% increase in UTS (matrix: ≈207 MPa; P6 premix: ≈282 MPa).
[0345] Example 17 - Effect of Nanostructured Premix on Grey Cast Iron (Alloy FC 200)
[0346] Test bars made of grey cast iron (ASTM A48 standard) and Y-blocks (alloy FC 200 - FUCO FC 200 matrix) were prepared using the cold box method.
[0347] Two tests were performed: Test 2 corresponded to a furnace "cleaning" melt and Test 3 corresponded to a melt in which a premix (Al from Alle) was added to the charge.
[0348] The content of niobium pentoxide (nanometer) was 0.1 mass % relative to the matrix material (corresponding to 0.07 mass % of Nb). The content of aluminum was 0.02 mass % relative to the matrix material. The content of the premix was 0.12 mass % relative to the matrix material.
[0349] The aluminum-containing powdered nano premix is added to the furnace. The premix is added 2 / 3 of the way through the melt, immediately after the scrap is added.
[0350] The inoculant was added to the bottom of the casting ladle before transferring the melt from the furnace (FeSiCaBaZr 0.30 mass %).
[0351] Molten charge 2: three FUCO FC 200 ingots + all carburizing agent (synthetic graphite with an incorporation efficiency of 98%) + all sulfur (CaS 0.8 mass%, which was taken out of the thermal analysis crucible) + all rod-shaped metallic tin (0.07 mass% Sn) + all 1020 scrap steel + 3 FUCO FC 200 ingots.
[0352] Molten charge 3: three FUCO FC 200 ingots + all carburizing agent (synthetic graphite with an incorporation efficiency of 98%) + all sulfur (CaS 0.8 mass%, which was taken out of the thermal analysis crucible) + all rod-shaped metal tin (0.07 mass% Sn) + all 1020 scrap steel + all premix (0.12 mass%) + 3 FUCO FC 200 ingots.
[0353] CaS was added after the first charge of FUCO was melted (after the first 3 ingots were melted).
[0354] The bath temperature in the furnace was about 1500±10°C. The pouring temperature was about 1400±10°C. The pouring time was about 15s. For the cooling time, the cooling time was overnight to room temperature. In the samples produced by the method of adding Nb, no premix floating was observed.
[0355] Improvement in fluidity during pouring was observed after increasing the melt pool and pouring temperatures. No carburizer was observed at the bottom of the furnace.
[0356] A reusable mold was removed after melting 50% of the FUCO charge to measure the chemical composition of the initial FUCO.
[0357] Mechanical evaluation: On average, P6 premix resulted in a 36.5% increase in UTS (matrix: ≈207 MPa; P6 premix: ≈282 MPa).
[0358] Mechanical evaluation of Y-blocks: On average, P6 premix resulted in a 12% increase in UTS (matrix: ≈276 MPa; P6 premix: ≈310 MPa).
[0359] Mechanical evaluation of test bars: On average, the P6 premix resulted in a 17% increase in UTS (matrix: ≈231 MPa; P6 premix: ≈270 MPa).
[0360] Example 18 - Effect of Nanostructured Premix on Grey Cast Iron (Alloy FC 200)
[0361] Test bars (ASTM A48 standard), Y-blocks and wedges made of grey cast iron (alloy FC 200-FUCOFC 200 matrix) were prepared. A cold box method was used.
[0362] Four tests were performed: Run 4 corresponds to baseline melting, Run 5 corresponds to melting with a substoichiometric premix (Al with Alle), Run 6 corresponds to melting with a stoichiometric premix (Al with Alle) and Run 7 corresponds to melting with a superstoichiometric premix (with Al from Alle) added to the charge.
[0363] The content of niobium pentoxide (nano) relative to the matrix material is 0.1 mass % (equivalent to 0.07 mass % Nb). The content of aluminum relative to the matrix material is 0.02 mass % (sub-condition), 0.034 mass % (stoichiometric) and 0.041 mass % (super-condition). The content of the premix relative to the matrix material is 0.120 mass % (sub-condition), 0.134 mass % (stoichiometric) and 0.141 mass % (super-condition).
[0364] A powdered nano premix containing aluminum was added to the furnace. The premix was added 2 / 3 of the way through the melt, immediately after the scrap was added.
[0365] The inoculant (FeSiCaBaZr 0.30 mass %) was added when the melt was transferred from the furnace to the casting ladle.
[0366] Molten charge 4: 50% of TAMBOR FC 200 ingots + all carburizing agent (synthetic graphite with an incorporation efficiency of 98%) + all sulfur (CaS 0.8 mass%) + all 1020 scrap steel + 50% of TAMBOR FC 200 ingots.
[0367] Molten charge 5: 50% of TAMBOR FC 200 ingot + all carburizing agent (synthetic graphite with incorporation efficiency of 98%) + all sulfur (CaS 0.8 mass%) + all 1020 scrap steel + all premix (0.120 mass%) + 50% of TAMBOR FC200 ingot.
[0368] Melt charge 6: 50% of TAMBOR FC 200 ingot + all carburizing agent (synthetic graphite with incorporation efficiency of 98%) + all sulfur (CaS 0.8 mass%) + all 1020 scrap steel + all premix (0.134 mass%) + 50% of TAMBOR FC200 ingot.
[0369] Molten charge 7: 50% of TAMBOR FC 200 ingot + all carburizing agent (synthetic graphite with incorporation efficiency of 98%) + all sulfur (CaS 0.8 mass%) + all 1020 scrap steel + all premix (0.141 mass%) + 50% of TAMBOR FC200 ingot.
[0370] The bath temperature in the furnace was about 1500±10°C. The pouring temperature was about 1400±10°C. The pouring time was about 15s. For the cooling time, the cooling time was overnight to room temperature. In the samples produced by the method of adding Nb, no premix floating was observed.
[0371] Improvement in fluidity during pouring was observed after increasing the melt pool and pouring temperatures. No carburizer was observed at the bottom of the furnace.
[0372] During the transfer step of the melt from the furnace to the casting ladle, one reusable mould is removed and during the transfer step from the ladle to the mould, the other is removed.
[0373] No significant changes in mechanical properties were observed.
[0374] Example 19 - Effect of Nanostructured Premix on Grey Cast Iron (Alloy FC 200)
[0375] Test bars (ASTM A48 standard) and wedges (alloy FC 200 - FUCO FC 200 matrix) made of grey cast iron were prepared using the cold box method.
[0376] Four tests were performed: Test 8 corresponds to a baseline melt, Test 9 corresponds to a melt with a substoichiometric premix (Al with Alle), Test 10 corresponds to a melt with a stoichiometric premix (Al with Alle) and Test 11 corresponds to a melt with a superstoichiometric premix (with Al from Alle), added to the charge.
[0377] The content of niobium pentoxide (nano) relative to the matrix material is 0.1 mass % (equivalent to 0.07 mass % Nb). The content of aluminum relative to the matrix material is 0.020 mass % (sub-condition), 0.034 mass % (stoichiometric) and 0.041 mass % (super-condition). The content of the premix relative to the matrix material is 0.120 mass % (sub-condition), 0.134 mass % (stoichiometric) and 0.141 mass % (super-condition).
[0378] A powdered nano premix containing aluminum was added to the furnace. The premix was added 2 / 3 of the way through the melt, immediately after the scrap was added.
[0379] The inoculant (FeSiCaBaZr 0.30 mass %) was added when the melt was transferred from the furnace to the casting ladle.
[0380] Melt charge 8: 50% of FUCO FC 200 ingots + all carburizing agent (synthetic graphite with an incorporation efficiency of 98%) + all 1020 scrap steel + 50% of FUCO FC 200 ingots.
[0381] Melt charge 9: 50% of FUCO FC 200 ingots + all carburizing agent (synthetic graphite with an incorporation efficiency of 98%) + all 1020 scrap steel + all premix (0.120 mass%) + 50% of FUCO FC 200 ingots.
[0382] Melt charge 10: 50% of FUCO FC 200 ingot + all carburizing agent (synthetic graphite with incorporation efficiency of 98%) + all 1020 scrap steel + all premix (0.134 mass%) + 50% of FUCO FC 200 ingot.
[0383] Melt charge 11: 50% of FUCO FC 200 ingot + all carburizing agent (synthetic graphite with an incorporation efficiency of 98%) + all 1020 scrap steel + all premix (0.141 mass%) + 50% of FUCO FC 200 ingot.
[0384] The bath temperature in the furnace was about 1500±10°C. The pouring temperature was about 1400±10°C. The pouring time was about 15s. For the cooling time, the cooling time was overnight to room temperature. In the samples produced by the method of adding Nb, no premix floating was observed.
[0385] Improvement in fluidity during pouring was observed after increasing the melt pool and pouring temperatures. No carburizer was observed at the bottom of the furnace.
[0386] During the transfer step of the melt from the furnace to the casting ladle, one reusable mould is removed and during the transfer step from the ladle to the mould, the other is removed.
[0387] No significant changes in mechanical properties were observed.
[0388] Example 20 - Effect of Nanostructured Premix on Grey Cast Iron (Alloy FC 200)
[0389] Test bars (ASTM A48 standard) and wedges (alloy FC 200 - FUCO FC 200 matrix) made of grey cast iron were prepared using the cold box method.
[0390] Four tests were conducted: Test 12 corresponded to the addition of 0.11 mass % micron-sized FeNb (0.1 mass % Nb) to the melt, Test 13 corresponded to the addition of 0.33 mass % micron-sized FeNb (0.3 mass % Nb) to the melt, Test 14 corresponded to the addition of 0.55 mass % micron-sized FeNb (0.5 mass % Nb) to the melt, and Test 15 corresponded to the addition of 1.1 mass % micron-sized FeNb (1 mass % Nb) to the melt, added to the charge.
[0391] Micron-sized FeNb was added to the furnace in powder form. The premix was added 2 / 3 of the way through the melt, immediately after the scrap was added.
[0392] The inoculant (FeSiCaBaZr 0.16 mass %) was added when the melt was transferred from the furnace to the casting ladle.
[0393] Molten charge 12: 50% of FUCO FC 200 ingot + all carburizing agent (synthetic graphite with an incorporation efficiency of 98%) + all 1020 scrap steel + FeNb 0.11 mass% + 50% of FUCO FC 200 ingot.
[0394] Molten charge 13: 50% of FUCO FC 200 ingot + all carburizing agent (synthetic graphite with an incorporation efficiency of 98%) + all 1020 scrap steel + FeNb 0.33 mass% + 50% of FUCO FC 200 ingot.
[0395] Molten charge 14: 50% of FUCO FC 200 ingot + all carburizing agent (synthetic graphite with an incorporation efficiency of 98%) + all 1020 scrap steel + FeNb 0.55 mass% + 50% of FUCO FC 200 ingot.
[0396] Molten charge 15: 50% of FUCO FC 200 ingot + all carburizing agent (synthetic graphite with incorporation efficiency of 98%) + all 1020 scrap steel + FeNb 1.1 mass% + 50% of FUCO FC 200 ingot.
[0397] The temperature of the molten pool in the furnace was about 1500±10°C. The pouring temperature was about 1400±10°C. The pouring time was about 15s. For the cooling time, the cooling time was overnight to room temperature. In the samples produced by the method of adding Nb, no FeNb floating was observed.
[0398] Improvement in fluidity during pouring was observed after increasing the melt pool and pouring temperatures. No carburizer was observed at the bottom of the furnace.
[0399] One reusable mould is removed during the transfer step of the melt from the furnace to the casting ladle and the other is removed during the transfer step from the ladle to the mould.
[0400] The mechanical properties are improved after adding micron-sized FeNb. Charge with 0.11 mass% FeNb: Ultimate tensile strength increased by 25.3%. Charge with 0.33 mass% FeNb: Ultimate tensile strength increased by 45.3%. Charge with 0.55 mass% FeNb: Ultimate tensile strength increased by 37.7%. Charge with 1.1 mass% FeNb: Ultimate tensile strength increased by 67.9%.
[0401] Example 21 - Effect of Nanostructured Premix on Grey Cast Iron (Alloy FC 200) - Variation of Nb2O5 Content
[0402] Test bars (ASTM A48 standard) and wedges (alloy FC 200 - FUCO FC 200 matrix) made of grey cast iron were prepared using the cold box method.
[0403] Four tests were conducted: Test 16 corresponds to a baseline melt, Test 17 corresponds to a melt with a superstoichiometric premix (with Alle's Al) of 0.1 mass % Nb2O5, Test 18 corresponds to a melt with a superstoichiometric premix (with Alle's Al) of 0.5 mass % Nb2O5 and Test 18 corresponds to a melt with a superstoichiometric premix (with Alle's Al) of 1 mass % Nb2O5, added together with the inoculant when transferring the melt from the furnace to the casting ladle.
[0404] The content of niobium pentoxide relative to the base material was 0.1 mass %, 0.5 mass % and 1.0 mass %.
[0405] The premix contents were 0.141 mass % (superconditioned), 0.703 mass % (superconditioned), and 1.406 mass % relative to the matrix material.
[0406] The inoculant (FeSiCaBaZr 0.16 mass %) was added when the melt was transferred from the furnace to the casting ladle.
[0407] Melt charge 16: 50% of FUCO FC 200 ingots + all carburizing agent (synthetic graphite with an incorporation efficiency of 98%) + all 1020 scrap steel + 50% of FUCO FC 200 ingots.
[0408] Melt charge 17: 50% of FUCO FC 200 ingot + all carburizing agent (synthetic graphite with incorporation efficiency of 98%) + all 1020 scrap steel + all premix (0.141 mass%) + 50% of FUCO FC 200 ingot.
[0409] Melt charge 18: 50% of FUCO FC 200 ingot + all carburizing agent (synthetic graphite with an incorporation efficiency of 98%) + all 1020 scrap steel + all premix (0.703 mass%) + FUCO FC 200 ingot.
[0410] Melt charge 19: 50% of FUCO FC 200 ingots + all carburizing agent (synthetic graphite with an incorporation efficiency of 98%) + all 1020 scrap steel + all premix (1.406 mass%) + 50% of FUCO FC 200 ingots.
[0411] The bath temperature in the furnace was about 1500±10°C. The pouring temperature was about 1400±10°C. The pouring time was about 15s. For the cooling time, the cooling time was overnight to room temperature. In the samples produced by the Nb addition method, premix floating was observed when 0.5 and 1.0% Nb2O5 were added.
[0412] Improvement in fluidity during pouring was observed after increasing the melt pool and pouring temperatures. No carburizer was observed at the bottom of the furnace.
[0413] During the transfer step of the melt from the furnace to the casting ladle, one reusable mould is removed and during the transfer step from the ladle to the mould, the other is removed.
[0414] No significant changes in mechanical properties were observed.
[0415] Example 22 - Effect of Nanostructured Premix on Grey Cast Iron (Alloy FC 200) - Variation of Nb2O5 Content
[0416] Test bars (ASTM A48 standard), Y-blocks and wedges made of grey cast iron (alloy FC 200-FUCO FC200 matrix) were prepared using the cold box method.
[0417] Four tests were conducted: Test 20 corresponds to a baseline melt, Test 21 corresponds to a melt with a substoichiometric premix (with Alle of Al) - 0.1 mass % Nb2O5 - added to the charge, Test 22 corresponds to a melt with a substoichiometric premix (with Alle of Al) - 0.1 mass % Nb2O5 - added in wire form and Test 23 corresponds to a melt with a substoichiometric premix (with Alle of Al) - 0.3 mass % Nb2O5 - added to the charge.
[0418] The contents of nano-Nb2O5 relative to the matrix material are 0.1%, 0.1% and 0.3% by mass respectively.
[0419] The contents of the premixes relative to the base material were 0.120 mass % (sub-condition), 0.120 mass % (sub-condition), and 0.361 mass % (sub-condition), respectively.
[0420] The inoculant (FeSiCaBaZr 0.16 mass %) was added when the melt was transferred from the furnace to the casting ladle.
[0421] Molten charge 20: 50% of FUCO FC 200 ingots + all carburizing agent (natural graphite) + all 1020 scrap steel + 50% of FUCO FC 200 ingots.
[0422] Melt charge 21: 50% of FUCO FC 200 ingots + all carburizing agent (natural graphite) + all 1020 scrap steel + all premix (0.120 mass %) + 50% of FUCO FC 200 ingots.
[0423] Melt charge 22: 50% of FUCO FC 200 ingot + all carburizing agent (natural graphite) + all 1020 scrap steel + all wire packaged premix (0.120 mass %) + 50% of FUCO FC 200 ingot.
[0424] Melt charge 23: 50% of FUCO FC 200 ingot + all carburizing agent (natural graphite) + all 1020 scrap steel + all premix (0.361 mass %) + 50% of FUCO FC 200 ingot.
[0425] The bath temperature in the furnace was about 1450±10°C. The pouring temperature was about 1390±10°C. The pouring time was about 15s. For the cooling time, the cooling time was overnight to room temperature. In the samples produced by the method of adding Nb, no premix floating was observed.
[0426] During the transfer step of the melt from the furnace to the casting ladle, one reusable mould is removed and during the transfer step from the ladle to the mould, the other is removed.
[0427] Mechanical evaluation of Y-blocks: On average, the sub-premix with 0.1% Nb2O5 resulted in a 9% decrease in UTS (matrix: 192 MPa; premix: 175.1 MPa) and the sub-premix with 0.3% Nb2O5 resulted in a 24% increase in UTS (matrix: 192; premix: 238.5 MPa).
[0428] Mechanical evaluation of test bars: On average, the sub-premix with 0.1% Nb2O5 resulted in a 12% decrease in UTS (matrix: 189.1 MPa; sub-premix: 166.7 MPa) and the sub-premix with 0.3% Nb2O5 resulted in a 19% increase in UTS (matrix: 189.1 MPa; premix: 225.6 MPa).
[0429] Example 23 - Comparison of Melts in Previous Examples
[0430] Comparing melts 0 to 15, Table 21 shows the summarized chemical composition of each melt:
[0431] Table 21 - Summary of the chemical compositions of the melts:
[0432] Melt %C %Si %Mn %P %S %Cr %Nb %Fe 00 3.52 2.21 0.24 0.01 0.01 0.02 <0.005 Matrix 01 3.45 2.3 0.24 0.01 0.01 0.03 <0.005 Matrix 02 3.47 1.93 0.25 0.01 0.01 0.02 <0.005 Matrix 03 3.4 1.99 0.21 0.01 0.01 0.02 <0.005 Matrix 04 3.21 2.05 0.48 <0.01 <0.01 0.08 0.009 Matrix 05 3.41 2.15 0.49 <0.01 <0.01 0.09 0.026 Matrix 06 3.3 2.17 0.53 <0.01 <0.01 0.08 0.041 Matrix 07 3.32 2.18 0.55 <0.01 <0.01 0.09 <0.035 Matrix 08 3.64 2.16 0.33 <0.01 <0.01 0.02 <0.005 Matrix 09 3.96 2.17 0.36 <0.01 <0.01 0.02 <0.005 Matrix 10 3.82 2.23 0.34 <0.01 <0.01 0.06 <0.005 Matrix 11 3.86 2.16 0.32 <0.01 <0.01 0.02 0.01 Matrix 12 3.59 2.2 0.35 <0.01 <0.01 0.02 0.09 Matrix 13 3.65 2.23 0.3 <0.01 <0.01 0.03 0.31 Matrix 14 3.55 2.14 0.34 <0.01 <0.01 0.03 0.56 Matrix 15 3.7 2.21 0.31 <0.01 <0.01 0.05 1.04 Matrix
[0433] Comparing melts 0 to 19, Table 22 shows the raw materials for each melt:
[0434] Table 22 - Raw materials for each melt
[0435]
[0436] Comparing Melts 0 to 19, Table 23 shows the details of the tested samples and the average ultimate tensile strength (UTS):
[0437] Table 23 - Test specimens and average ultimate tensile strength (UTS):
[0438]
[0439]
[0440] Fig.31 A comparison graph of the average ultimate tensile strength (UTS) results for Melts 0 through 19 shown in Table 23 is shown.
[0441] Those skilled in the art will appreciate the knowledge disclosed herein and be able to reproduce the invention in the disclosed embodiments and other variations and alternatives that fall within the scope of the following claims.
Claims
1. Cast iron, characterized in that It contains niobium particles in a concentration of 0.01 to 1 mass %.
2. The cast iron according to claim 1, characterized in that The cast iron contains niobium particles in a concentration of 0.03 to 0.3 mass %.
3. The cast iron according to claim 1, characterized in that The cast iron also contains aluminum in a concentration of 0.01 to 1 mass %.
4. The cast iron according to claim 3, characterized in that The cast iron contains aluminum in a concentration of 0.01 to 0.044 mass %.
5. The cast iron according to claim 1, characterized in that The niobium particles are particles with a particle size distribution characteristic in the nanometer range.
6. The cast iron according to claim 5, characterized in that The niobium particles are niobium pentoxide nanoparticles or FeNb nanoparticles.
7. The cast iron according to claim 1, characterized in that The cast iron is ductile iron or grey cast iron.
8. A method for obtaining cast iron, characterized in that The method comprises adding niobium particles at a concentration of 0.01 to 1 mass % prior to pouring the molten matrix.
9. The method for obtaining cast iron according to claim 8, characterized in that The niobium particles are particles with a particle size distribution characteristic in the nanometer range.
10. The method for obtaining cast iron according to claim 8, characterized in that The step of adding niobium particles is performed by adding a premix comprising niobium particles and aluminum particles.
11. The method for obtaining cast iron according to claim 10, characterized in that The aluminum is in the form of powder, crushed, ground or shredded.
12. The method for obtaining cast iron according to claim 10, characterized in that The premix is added in at least one of the following ways: - Added to the mold before pouring the melt; - Added to the transfer ladle before pouring the melt; - Add at the entrance of the mold feed channel before pouring the melt; - Added to the furnace before pouring the melt; or - Added to the spray stream together with the inoculant.
13. The method for obtaining cast iron according to claim 10, characterized in that The premix contains Nb2O5 and Al / Nb2O5 in a molar ratio of 1 to 5.
14. The method for obtaining cast iron according to claim 8, characterized in that It also includes the step of adding an inoculant.
15. The method for obtaining cast iron according to claim 8, characterized in that It also includes the step of adding a carburizing agent to the molten charge.
Citation Information
Patent Citations
PREMIX CONTAINING NANOPARTICLES, INDUSTRIAL PROCESS FOR INCORPORATING NANOPARTICLES INTO PRODUCTS OF ECONOMIC INTEREST
BR102022002639A2
Process for welding low-alloy steels containing niobium
US3860777A
Lead-containing additive for steel melts
US4892580A
